Driving sustainable waste management: The role of local champions and social media engagement - Firmansyah Adi; Sadono Dwi (BIO Web of Conferences)
This study explored the effects of local champions and social media on shaping perceptions and behaviors related to domestic waste management across nine villages in West and East Java, Indonesia. Employing a quantitative approach, the research engaged 245 respondents involved in a waste management assistance program. Structural Equation Modeling (SEM) analysis revealed that both local champions and social media play essential roles in enhancing waste management perceptions and behaviors. Local champions significantly influenced perceptions and behaviors, while social media had a more substantial effect on perceptions and behaviors. Social media platforms offer a cost-effective method for reaching broader audiences, facilitating real-time communication, and promoting awareness of sustainable waste management. The results emphasize the crucial significance of embedding local champions into digital platforms to promote sustainable waste management practices. This study offers important findings for government officials to strengthen waste management strategies through the synergistic use of local champions and social media engagement.